1994
DOI: 10.1093/hmg/3.8.1275
|View full text |Cite
|
Sign up to set email alerts
|

Released chromatin: linearized DNA for high resolution fluorescence in situ hybridization

Abstract: Free DNA was prepared from routinely harvested and fixed cells for high resolution FISH mapping using either a sodium hydroxide/ethanol mixture or 70% formamide. Hybridization signals from cosmid probes appeared as extended lines. The average length of signals on DNA prepared with sodium hydroxide was significantly greater than with formamide. A set of overlapping cosmids from the HLA class II region was used to determine how precisely the actual overlap or gap between probes can be calculated from the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The chromosome preparations were then fixed in methanol for 30 min at -20°C. Chromatin fibers were prepared essentially as described by Senger et al (1994). Exponentially growing cells were harvested and fixed in Carnoy's fixative.…”
Section: In Situ Hybridization and G-bandingmentioning
confidence: 99%
“…The chromosome preparations were then fixed in methanol for 30 min at -20°C. Chromatin fibers were prepared essentially as described by Senger et al (1994). Exponentially growing cells were harvested and fixed in Carnoy's fixative.…”
Section: In Situ Hybridization and G-bandingmentioning
confidence: 99%
“…The authors speculated that, with multicolor FISH, free chromatin mapping would readily resolve gene sequences separated by as little as 10 kb (Heng et al 1992). Soon thereafter, Senger et al (1994) and Fidlerova et al (1994) demonstrated the use of a sodium hydroxide/ethanol mixture or 70% formamide to prepare chromatin fibers which they called "free DNA." Hybridization signals from cosmid probes appeared as extended lines and overlaps between clones were determined using the lengths of the probe signals and their known kilobase size as an internal standard.…”
Section: Dna Fiber Mappingmentioning
confidence: 99%
“…Pixel data of fluorescence images were converted into physical lengths of DNA stretches as follows: first the relative lengths of signals and gaps as the unstained chromosome region between two signals were determined as described by Sjöberg et al (1997) to neutralize artificial differences due to the shape of pixels. Subsequently, the size of a gap flanked by a red and a green signal was estimated using probe size standards (PSS; Heiskanen et al, 1994;Senger et al, 1994;Florijn et al, 1995). Each probe served as PSS to measure the size of cohybridizing probes.…”
Section: In Situ Hybridization Detection and Analysis Of Signalsmentioning
confidence: 99%